Penerapan Senam Hamil sebagai Upaya Persiapan Fisik dalam Menghadapi Persalinan - Fatimah, Siti; Rohmah, Siti (Universitas Baiturrahim, 2025)
Optimal physical preparation is essential for pregnant women in facing the labor process. A lack of knowledge and physical activity during pregnancy may increase the risk of delivery complications and prolong the duration of labor itself. One proven effective intervention is pregnancy exercise, which helps strengthen the muscles used during childbirth, improves body flexibility, and reduces anxiety. This community service activity aimed to enhance the knowledge and skills of pregnant women in performing pregnancy exercises as a physical preparation for labor. The activity was carried out in the working area of Puskesmas Sindangkasih using an educational approach combined with practical sessions. The methods included counseling,and demonstrations.. Evaluation was conducted through pre- and post-tests as well as observation of participants' practical skills. The results showed a significant improvement in knowledge, with a 46% increase, and in the ability of pregnant women to perform the exercises correctly. Participants also reported increased self-confidence and physical readiness for childbirth. In conclusion, the structured and continuous implementation of pregnancy exercise can serve as an effective strategy to improve the physical readiness of pregnant women in facing the childbirth process.